2016
DOI: 10.1007/s00484-016-1282-0
|View full text |Cite
|
Sign up to set email alerts
|

A simple approach for the development of urban climatic maps based on the urban characteristics in Tainan, Taiwan

Abstract: Motivated by the increasing thermal load in urban environment, this work established Urban Climatic map (UCmap) focusing on thermal environment issues based on urban development factors, e.g., land cover and building characteristics, representing thermal load of human body and ventilation path in the urban structures. In the established process of UCmap in this work, Tainan city, which is a highly developed city in southern Taiwan, is selected as the research area. A 50-m resolution grid is used to capture urb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 50 publications
1
12
1
Order By: Relevance
“…This finding is partly inconsistent with previous studies, which have indicated an increase in temperature with building density (e.g. Chen, Lin, & Lin, 2017 ; Shi, Lau, Ren, & Ng, 2018 ; Wong & Yu, 2005 ), building height ( Yang et al, 2019 ) and street openness ( Ali-Toudert & Mayer, 2006 ) in hot to warm climates. Previous research has also observed higher temperature at densely developed high-rise buildings owing to lower ventilation efficiency ( Yang et al, 2019 ); or at openly distributed low-rise buildings due to increase of incoming solar radiation heating up street canyons ( Ali-Toudert & Mayer, 2006 ; Shi et al, 2018 ; Thorsson, Lindberg, Björklund, Holmer, & Rayner, 2011 ).…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is partly inconsistent with previous studies, which have indicated an increase in temperature with building density (e.g. Chen, Lin, & Lin, 2017 ; Shi, Lau, Ren, & Ng, 2018 ; Wong & Yu, 2005 ), building height ( Yang et al, 2019 ) and street openness ( Ali-Toudert & Mayer, 2006 ) in hot to warm climates. Previous research has also observed higher temperature at densely developed high-rise buildings owing to lower ventilation efficiency ( Yang et al, 2019 ); or at openly distributed low-rise buildings due to increase of incoming solar radiation heating up street canyons ( Ali-Toudert & Mayer, 2006 ; Shi et al, 2018 ; Thorsson, Lindberg, Björklund, Holmer, & Rayner, 2011 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Urbanization leads to changes in land use and cover [5,6], mainly manifesting as the replacement of large natural surfaces with impermeable surfaces and buildings. In addition, with the constant large number of people moving to urban areas, building density and human activity intensity also increases [7,8]. Rapid urban expansion directly alters local climate and hydrological systems [9] due to a variety of urban environmental problems, among which the intensification of the urban heat island (UHI) has attracted wide attention.…”
Section: Introductionmentioning
confidence: 99%
“…Study sites of Hong Kong ( a ) and Tainan ( b ) in the first survey (for both maps, darker colors in the legend indicate urban areas with higher density. Please refer to [39,40] for further information).…”
Section: Figurementioning
confidence: 99%